Circulating Current Reduction for Photovoltaic Parallel Modular Inverters Using Modified Space Vector Modulation - Choi, Hye Won; Lee, Kyo Beum (2022 IEEE Energy Conversion Congress and Exposition, ECCE 2022, 2022)
This paper proposes a circulating current reduction method for photovoltaic parallel modular inverters using modified space vector modulation. The modular inverters are widely used in high power applications to increase the rate of power and capacity of the systems due to the adjustable power rating. However, a circulating current is generated, when each inverter has imperfect symmetry in hardware. The circulating current causes output current distortion and the decrease in reliability. The proposed modulations reduce effectively the low frequency (LF) circulating current to improve the reliability of systems. The proposed method is classified into two regions according to the modulation index range. The LF circulating current is evaluated by the reduction method and modulation regions. The feasibility of proposed reduction method is verified by simulation results.
Keywords: Circulating current; Circulating current reduction; Five level inverter; Lower frequencies; Modulars; Parallel inverter; Photovoltaic systems; Photovoltaics; Reduction method; Space Vector Modulation; Circulating current; Five-level inverter; Parallel inverter; Photovoltaic system; Space vector modulation